Measuring Purchase Decisions Based on Product Quality and Price - Harahap, Rifkah Aqila; Hidayat, Rahmat (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of product quality and price on consumer purchasing decisions. There are three variables observed in this study, namely product quality, price, and purchasing decisions. Data was collected by distributing questionnaires to 86 respondents who participated in the study, using purposive sampling as the sampling technique. The validity and reliability of the research questionnaire were also tested. The data analysis technique used in this study was quantitative descriptive analysis using multiple linear regression with SPSS as the analysis tool. Hypothesis testing was conducted using the coefficient of determination test, simultaneous test, and partial test, using model feasibility tests, namely: P-Plot normality test, Kolmogorov-Smirnov normality test, and linearity test. The research results indicate that product quality and price influence purchasing decisions. Although the results obtained from the research are quite good, this study has several limitations. It focuses solely on product quality and price as factors influencing purchasing decisions, while other factors may also play a role in consumer decisions, such as promotions, particularly those using social media. Therefore, the results of this study may not fully reflect the complexity of the consumer decision-making process. For this reason, the researcher recommends that SMEs should carefully consider pricing and product quality improvements to maintain a positive impression of the burger products that define the SME's identity.